2016
DOI: 10.1038/mp.2016.120
|View full text |Cite
|
Sign up to set email alerts
|

HPA axis in major depression: cortisol, clinical symptomatology and genetic variation predict cognition

Abstract: The Hypothalamic Pituitary Adrenal (HPA) axis has been implicated in the pathophysiology of a variety of mood and cognitive disorders. Neuroendocrine studies have demonstrated HPA axis overactivity in major depression, a relationship of HPA axis activity to cognitive performance, and a potential role of HPA axis genetic variation in cognition. The present study investigated the simultaneous roles HPA axis activity, clinical symptomatology, and HPA genetic variation play in cognitive performance. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
341
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(359 citation statements)
references
References 60 publications
10
341
2
6
Order By: Relevance
“…Cortisol levels were found to be elevated in psychotic depression and correlated negatively with verbal memory and processing speed across all subjects. This finding was recently replicated and extended to implicate genetic variation in psychotic depression as a mechanism for the relationship between cortisol and cognitive performance (Keller et al 2017). …”
Section: Introductionmentioning
confidence: 76%
“…Cortisol levels were found to be elevated in psychotic depression and correlated negatively with verbal memory and processing speed across all subjects. This finding was recently replicated and extended to implicate genetic variation in psychotic depression as a mechanism for the relationship between cortisol and cognitive performance (Keller et al 2017). …”
Section: Introductionmentioning
confidence: 76%
“…Prior studies have shown that prenatal Dex exposure can result in increased hypothalamic-pituitary-adrenal (HPA) activity (35,36). The data from human and animal studies have shown that higher HPA activity contributes to major depressive disorders (MDD) (37,38). We therefore examined circulating corticosterone level in F1 and F2 offspring.…”
Section: Prenatal Dex Exposure Increases Crhr1 Gene Expression In Hipmentioning
confidence: 99%
“…Conversely, people with depression and a history of childhood trauma may have blunted cortisol responses to stress, compared to those with depression and no early-life trauma 128. Stress-induced HPA axis alterations appear interrelated with cognitive function,129 as well as depression subtype or variation in HPA-related genes 130. Stress also has short- and long-term impairing effects on neurogenesis131 and other neural mechanisms 132.…”
Section: Introductionmentioning
confidence: 99%